2011
DOI: 10.1007/s10549-011-1602-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of the renin–angiotensin system genes and breast cancer risk: a meta-analysis

Abstract: The renin-angiotensin system (RAS) has been considered to be implicated in the development of breast cancer. However, the results are inconsistent. In this study, we conducted a meta-analysis to assess the association between four polymorphisms, including angiotensin I-converting enzyme (ACE) I/D and A240T, angiotensin II type 1 receptor (AGTR1) A1166C and angiotensinogen (AGT) M235T polymorphisms, and breast cancer risk. Published literature from PubMed, ISI web of science, and Embase databases were retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
3
20
1
Order By: Relevance
“…Our findings are in agreement with prior studies that have found an association between this polymorphism and DM2 (Young et al, 1998;Mehri et al, 2010). Additionally, meta-analyses have also reported associations between the A allele of the polymorphism and the risk of cardiovascular diseases Pan, 2012, 2013;Liang et al, 2013a,b;Li et al, 2013;Chen et al, 2014), renal failure (Zhou et al, 2013b), pre-eclampsia (Lin et al, 2012), and breast cancer (Xi et al, 2011). However, a meta-analysis involving Caucasian and Asian individuals failed to detect an association between the rs699 polymorphism and diabetic nephropathy (Ding et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in agreement with prior studies that have found an association between this polymorphism and DM2 (Young et al, 1998;Mehri et al, 2010). Additionally, meta-analyses have also reported associations between the A allele of the polymorphism and the risk of cardiovascular diseases Pan, 2012, 2013;Liang et al, 2013a,b;Li et al, 2013;Chen et al, 2014), renal failure (Zhou et al, 2013b), pre-eclampsia (Lin et al, 2012), and breast cancer (Xi et al, 2011). However, a meta-analysis involving Caucasian and Asian individuals failed to detect an association between the rs699 polymorphism and diabetic nephropathy (Ding et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Zhang et al (2013) observed that it may be involved in the development of coronary heart disease, while Zhang et al (2011) reported a lack of association with susceptibility to ischemic stroke. In addition, Xi et al (2011) demonstrated that it might be implicated in the pathogenesis of breast cancer, and Ding et al (2012) established its possible contribution to the development of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The A1166C polymorphism (rs5186) is located in the 3' untranslated region, and comprises an A to C transversion at nucleotide 1166. Previous studies have demonstrated that this sequence variation is associated with susceptibility to coronary heart disease, breast cancer, and diabetic nephropathy (Xi et al, 2011;Ding et al, 2012;Zhang et al, 2013). However, little is known regarding the association between the AGTR1 gene A1166C polymorphism and susceptibility to IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…This study is an update meta-analysis in which the results were different from the previous one. 25 Previous studies suggested that the RAS plays an important role in the regulation of cell proliferation, angiogenesis, and inflammation, 27,28 which indicated that RAS genes might be implicated in the carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, there are several studies that had not been included in their meta-analysis. In the present study, we included five case-control studies to perform a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%